Kedudukan Peraturan Pemerintah Pengganti Undang-Undang di Tinjau Dari Hierarki Perundang-Undangan Indonesia - Hanum, Roro Hanum; Murdiana, Elfa; Bahari, Raha (IAIN Metro, 2023)
Abstrak : In the context of law and regulations in Indonesia, the concept of hierarchy is vital for ensuring control over regulations that could potentially harm society both materially and non-materially. This concept is rooted in Hans Kelsen's theory of legal norms, which posits that legal norms have hierarchical levels, with grundnorms at the top. These norms are interrelated and form a coherent legal order. However, the application of this hierarchy is influenced by political factors that shape the constitutional system.One significant legal instrument reflecting this hierarchy in Indonesia is the Government Regulation in Lieu of Law (Perppu), which holds an equivalent position to regular laws in the Indonesian presidential system. It is essential to clearly define the term